Implementation of Islamic Religious Education in the Industrial Era 4.0: Opportunities, Challenges, and Adaptation Strategies - Rifdillah, Muhammad (At-tadzkir: Islamic Education Journal, 2025)
This study investigates the implementation of Islamic Religious Education (IRE) in the era of Industrial Revolution 4.0, focusing on its opportunities, challenges, and adaptive strategies. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis in selected madrasahs and Islamic higher education institutions in Banten Province. The results show that digital transformation opens vast opportunities for interactive, student-centered, and technology-integrated learning in IRE. However, teachers still face challenges related to limited digital literacy, unequal infrastructure, and the risk of declining spiritual interaction between educators and learners. The study finds that institutions have developed adaptive strategies, including digital literacy training, the integration of Islamic values into technology-based curricula, and the adoption of hybrid learning models that combine technological innovation with spiritual guidance. The findings highlight that the success of IRE in the digital era depends not only on mastering technology but also on maintaining the spiritual and ethical foundations of Islamic pedagogy. Therefore, this study proposes a model of value-based digital transformation, positioning technology as an instrument (wasilah) to strengthen, rather than replace, the moral mission of Islamic education.